Comparison Of Autoclave And Vacuum Oven Treatment On Rice Bran Stability And Chemical Properties - Badri, Nur Alisa Abdul Mutalib @ Ahmad (Universiti Sains Malaysia, 2020)
Heat stabilization of rice bran has been widely used to inactivate the enzyme activity which able to delay the deterioration and prolong the shelf life of the rice bran. However, there are no reports in the literature of using vacuum drying to stabilize rice bran. The purpose of this research is to compare the performance of rice bran stabilization by using autoclave treatment (120˚C, 20 minutes) and vacuum drying in terms of rice bran stability and chemical properties. Respond surface methodology (RSM) with the application of central composite design (CCD) and desirability function was used to determine the optimum condition to stabilize rice bran by using vacuum drying. The optimization factors were drying temperature (40-90˚C) and time (10-20 min) while the investigated responses were moisture content, crude fat, crude protein, FFA value, lipase activity, peroxide value and γ-oryzanol content. The chemical properties and storage stability of rice bran stabilized by autoclave treatment and optimized vacuum drying were evaluated and compared. Drying temperature of 90˚C and drying time of 10 min was found to be optimum for minimum moisture content, maximum crude fat, maximum crude protein, FFA value at 5%, minimum lipase activity, minimum peroxide value and maximum γ-oryzanol content. There was a significant difference (p<0.05) between autoclaved and vacuum dried rice bran in terms of moisture content, crude fat and crude protein while no significant difference (p<0.05) was observed between the effect of treatments on the γ-oryzanol content. Rice bran stabilized either by autoclave treatment or vacuum drying is effective in inactivating the lipase and lipoxygenase enzyme for its safe storage of up to 3 months.